PENGARUH PARIWISATA TEMAJUK DAN PEMBERDAYAAN EKONOMI TERHADAP KESEJAHTERAAN MASYARAKAT SAMBAS - Meriyanti, Meriyanti; Aminuyati, Aminuyati; Herkulana, Herkulana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis is entitled "The Effect of Temajuk Beach Tourism and Economic Empowerment on Community Welfare in Paloh Subdistrict of Sambas Regency" This study aims to analyze the influence of Temajuk Beach Tourism and Economic Empowerment on Community Welfare, The research method used in this study is the exspos facto research method. The source of data in this study is the coastal community of Temajuk village, Paloh, Sambas district. Based on the results of testing the hypothesis, it can be concluded that the testing individually (partial) of the variable influence of tourism on community welfare is 63.5%, and the magnitude of the influence of economic empowerment on welfare is 34.5% while for testing together (simultaneous) of the variables of tourism and economic empowerment has a positive and significant effect directly on the welfare of the community that is equal to 49.39%.Â Keywords: Beach Tourism, Economic Empowerment, Community welfareÂ